FACTORS AFFECTING THE BIOAVAILABILITY OF DRUGS - Rakhimova Gulnora; Maksudova Firuza Khurshidovna; Rakhimova Oygul; Azimova Nargiza Abbaskhanovna; Lure Mark Yevgenevich (Web of Journals Publishing, 2025)
Excipients, having certain physicochemical properties and constantly contacting with the drug, can have different effects depending on the conditions. Being inactive from a pharmacological point of view, excipients, in one way or another, affect the "drug - macroorganism " system. Approximately 40% of new chemical compounds that have shown pharmacological activity during screening have low solubility in water. Such compounds belong to classes II and IV according to the biopharmaceutical classification system. The difficulty of the transition of the drug into solution causes the lack of correlation between the dose and the pharmacological effect, low bioavailability, and, as a consequence, a decrease or distortion of the pharmacological effect.
Keywords: Pharmacokinetics, bioavalability, excipients, drug delivery systems, solid dispersion systems.